Espiritualidade e internet: análise de uma experiência mística através do correio eletrônico. - Avellar, Valter Luís de (2009)
This research aims at understanding why so many people use Internet e-mail in order to divulge positive attitudes, positive values, optimism, wisdom, spirituality and meaning of life messages. What does motivate them and which are the effects in their lives? Departing from a humanistic and spiritual messages exchange group experience, we will deal with some aspects regarding to this Internet phenomenon. In order to focus sociability through network, we will employ Cyberspace, Cyberculture and Collective Intelligence concepts. The propagation of faith will be made through Mystic and Sacred optic. Transdisciplinarity will work as support for interreligious dialogue that becomes, by itself, evident. And, at least, we will analyze therapeutic effects, through a kind of human knowledge, denominated Logotherapy.